Hhstyle.com : Tokio, Japón. 1999-2000 - Kazuyo Sejima & Associates (2004)
Local para exposición y venta de muebles de importación vinculado a la venta por Internet.
Keywords: SEJIMA, KAZUYO; JAPON; TOKYO; ARQUITECTURA COMERCIAL; LOCALES COMERCIALES; SHOWROOMS; CONSTRUCCION; CERRAMIENTOS; VIDRIO; CHAPA; ESTRUCTURAS METALICAS